Social Movements in India: A Review of Literature - Shah,G. (Jaipur Rawat, 2024)
Social movements primarily take the form of non-institutionalised collective political action which strive for political and/or social change. While India has witnessed many such movements over the centuries, it is only recently that scholars have begun to study them in depth. This thoroughly revised and updated version of a seminal book divides studies on social movements in India into nine categories based on the participants and issues involved: peasants, tribals, dalits, backward castes, women, students, middle class, working class, and human rights and environmental groups. Each of the nine chapters is divided according to the major components of most social movements: issues, ideology, organisation and leadership. Based on these divisions, Professor Shah critically examines and reviews the literature concerning social movements in India from 1857 to the present. In the process he discusses the theoretical issues raised by various scholars while analysing major trends in different movements. In conclusion, he suggests areas for future research. Proposing a logical classification of social movements in modern India, this book will be widely welcomed by social activists as well as by political scientists, historians and sociologists. It will also be invaluable as a text in courses on social movements.
India
WORDI/2024/CRB/1362